2021
DOI: 10.21203/rs.3.rs-476628/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Elk1/MMP-9 Axis Regulates E-Cadherin and Occludin in Ventilator-Induced Lung Injury

Abstract: Background: Ventilator-induced lung injury (VILI) is a common complication in the treatment of respiratory diseases with high morbidity and mortality. Matrix metalloprotein (MMP) 9 and Elk1 are involved in VILI, but the roles have not been fully elucidated. This study examined the mechanisms of the activation of MMP-9 and Elk1 regulating barrier function in VILI in vitro and in vivo.Methods: For the in vitro study, MLE-12 cells were pre-treated with Elk1 siRNA or MMP-9 siRNA for 48 h prior to cyclic stretch at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Reactive oxidants and free radicals can directly obstruct cell function, causing proteases, such as MMP-9, to be released. MMP-9 serves a role in various physiological processes, including extracellular matrix degradation and lung tissue remodeling (42)(43)(44), both of which have been reported to be associated with the occurrence of various lung diseases including chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis (42)(43)(44). MMP9 activity is regulated by the specific endogenous inhibitor TIMP1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxidants and free radicals can directly obstruct cell function, causing proteases, such as MMP-9, to be released. MMP-9 serves a role in various physiological processes, including extracellular matrix degradation and lung tissue remodeling (42)(43)(44), both of which have been reported to be associated with the occurrence of various lung diseases including chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis (42)(43)(44). MMP9 activity is regulated by the specific endogenous inhibitor TIMP1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…SREBF1 [747], ELF5 [748], TP53 [749], EGR1 [750], E2F6 [751] and STAT3 [752] have been demonstrated to function in cardiovascular diseases, but these genes might be involved in the progression of COVID-19. ELK1 [753], EGR1 [754] and STAT3 [755] plays a key role in the development of the lung diseases, but these genes might be involved in the progression of COVID-19. Previous studies have reported that EGR1 [756], FOXL1 [757] and STAT3 [758] exhibit significant associations with liver injury, but these genes might be involved in the progression of COVID-19.…”
Section: Mirna-hub Gene Regulatory Network Constructionmentioning
confidence: 99%